Pengaruh Kinerja Front Office Department Terhadap Kepuasan Tamu di Hotel Grand Arkenso Parkview Semarang - Alamsyah, Muhammad Chairul; Aprilliyani, Renny (Mahesa Research Center, 2024)
This research aims to evaluate the direct impact of Front Office Department performance on guest satisfaction. The research method used is a quantitative method with regression analysis. This research sample involved 232 respondents who were hotel guests who stayed at the hotel during the research period. Data was collected through a questionnaire that focused on guest perceptions of FOD performance and satisfaction levels.Research confirms that the performance of the Front Office Department has a significant effect on guest satisfaction. From the regression analysis, a positive relationship can be seen between performance and guest satisfaction with the regression equation Y = 13,047 + 0.570(X). The F test showed statistical significance (F = 109.830, p < 0.05), and the Coefficient of Multiple Determination (R2) of 56.8% indicated that most of the variation in guest satisfaction could be explained by performance. Reliability results confirm the consistency and reliability of the data.The conclusion is that performance has a crucial role in increasing guest satisfaction at the Grand Arkenso Parkview Hotel Semarang. Factors such as efficiency of the check-in/check-out process, friendliness of staff, handling of complaints and accuracy of information appear to have a significant impact. These findings provide in-depth insight into improving services to achieve higher guest satisfaction, which can ultimately strengthen guest loyalty and the hotel's image in the market. It also provides a basis for future service improvements and technology implementation